Interpretation of the Mathematical Geometry of the Roti Canai Structure in North Sumatra - Aprilia Sabela; Indri Yonisa Br Sembiring; Novi Fhitri Ade; Yulinar Naibaho (LPPM UIKA Bogor, 2023)
This research was aimed at finding out the role of mathematical geometry in the process of making delicious Roti Canai. This research uses a literature review method or what is usually called library research which uses library materials such as books, magazines, documents, and journal articles. The results of this research show that there is a role of mathematical geometry in making Roti Canai, which includes a circular shape (π), structure, weight, and temperature measurement. From all the involvement of geometry in the process of making Roti Canai, delicious Roti Canai is created. So, it is concluded that the role of geometry is very important in the process of making Roti Canai.